The adoption of smart warehouse in Shah Alam: A qualitative study on the decisive factors - Ooi, Jia Xiang; Pang, Xiao Tong; Teng, Zi Xuan (2023)
The adoption of smart warehouse has been an emerging trend, especially in other foreign countries, due to the boom in the e-commerce, online retailing as well as the emergence of industry 4.0. However, there is a lack of warehouse in Malaysia that adopt the use of smart warehouse, and many are still on manual operation. Therefore, the purpose of this research is to study the determinant factors that influence the adoption of smart warehouse within warehouse operators that operates in Shah Alam. There are three objectives in this research in tandem with the main goal. Firstly, to assess the current technologies used in warehouses in Shah Alam that can be linked back to smart warehouses. Secondly, to identify the factor that influences organizational readiness towards smart warehousing. Thirdly, to understand the external environment factors that could support the implementation of smart warehouse. Researchers utilize qualitative method in the form of interview question to acquired data. TOE framework has been employed by the researchers to analyse and represent the findings for this study. Lastly, by offering insight into the factors that influence adoption, this study has iii contributed to encourage Malaysian warehouses to adopt smart warehouse approaches